PENGGUNAAN ANALISIS ABC UNTUK PENGENDALIANPERSEDIAAN BARANG HABIS PAKAI : STUDI KASUS DI PROGRAM VOKASI UI - Wahyuni, Titis (Jurnal Vokasi Indonesia, 2015)
The purpose of this study was to determine the consumable inventory control are applied in Vocational Education Program, University of Indonesia as well as to determine the consumable inventory into groups A, B, and C based on the use of the ABC analysis, investing, and the critical index. This research uses descriptive analytical approach to look at the problems faced and the activities undertaken by the Procurement Section vocational program UI to manage inventory of consumable during 2014. The supply of consumable goods data is processed to provide a picture of the pattern of inventory consumable goods then the classification method ABC analysis of demand, investment, and the critical index. This research will also produce an application used to manage the supply of consumables in the vocational program UI. Results from this study is the control of the supply of consumables in the vocational program UI is sufficient. ABC analysis of the results obtained that the demand for consumables inventory categories are included in the group A are as many as nine items, group B were 26 items, and group C as many as 125 items. A total of 78.74% of the demand comes only 9 items and 5.11% request came from 125 items of goods. ABC analysis of the results obtained that the investment value of inventory categories consumables are included in the group A are as many as 18 items, group B a total of 29 items, and group C as many as 113 items. A total of 79.94% of investment value is only given to 18 items and 5.01% of investment value given for 113 items. From the analysis of the critical index ABC found that as many as 11 items of inventory consumable goods that enter the group A has an investment of 79.94%, 67 inventory items consumable goods that enter the group B has an investment of 15.06%, and 82 items supply of consumable goods that enter the group C has an investment value amounting to 5.01%.